Influence of age at slaughter and sex on carcass characteristics, meat quality, fatty acids, and ribonucleotides in white-tailed yellow native chickens - Chaosap, Chanporn; Sivapirunthep, Panneepa; Adeyemi, Kazeem D. (My University, 2024)
This study investigated the effects of age and sex on carcass and meat characteristics of one of Thailand’s major indigenous chicken breeds, the white-tailed yellow native chicken (NC). A total of 120 one-day-old NC (60 males and 60 females) were raised, and harvested at either 16, 20 or 24 weeks. The results showed that body, carcass, breast and fillet weights did not differ (P > 0.05) between 16- and 20-week-old NC, but were lower (P < 0.05) than those of 24-week-old NC. Male NC had higher (P < 0.05) body, carcass, wing, back and thigh weights than female NC. Neither sex nor age affected muscle pH, sarcomere length, redness and yellowness, guanosine monophosphate, and hypoxanthine. The interaction between age and sex was significant (P < 0.05) for %dressing, %leg, L*, C14:1, C18:1n9 and C20:4n6. Shear force was lower in 16-week-old NC (P < 0.05). The 24-week-old NC had lower (P < 0.05) C13:0, C16:0, C18:0, C18:2n6t, C20:4n6, C22:6n-3, intramuscular fat and inosine 5’-monophosphate levels and higher (P < 0.05) C18:2n6c, C18:3n-3 and C20:3n-6 levels than the 16- and 20-week-old NC. Male NC had higher (P < 0.05) C13:0-, C14:0-, C18:2n6t-, C20:3n-6- and lower inosine levels than female NC. In conclusion, these data highlight age- and sex-specific differences in carcass and meat quality of NC and provide relevant information to support consumer-oriented decisions on the production, processing and nutritional value of NC.
Keywords: Dressing percentage; Inosine-5'-monophosphate; Sarcomere length; Shear force